The Association Between Gelsolin-like Actin-capping Protein (CapG) Overexpression and Bladder Cancer Prognosis - Bahrami, Samira; Gheysarzadeh, Ali; Sotoudeh, Mehdi; Bandehpour, Mojgan; khabazian, Reza; Zali, Hakimeh; Hedayati, Mehdi; Basiri, Abbas; kazemi, Bahram (Urology Journal, 2020)
Purpose: Muscle-invasive bladder cancer (MIBC) is associated with disease progression and metastasis leading to poor prognosis. Current chemotherapy approaches have not adequately increased patient survival. Therefore, in this study, tissue proteome of patients with MIBC was performed to introduce possible protein candidates for bladder cancer prognosis as well as targeted therapy. Materials and Methods: After obtaining tumoral and non-tumoral tissues of MIBC patients, and normal bladder tissue of non-bladder cancer patients, two-dimensional gel electrophoresis (2-DE) and liquid chromatography-mass spectrometry (LC-MS/MS) were used to analyze tissue proteome. Gelsolin-like Actin-capping (CAPG) protein was further examined using Real-time PCR and western blot analysis. Results: The 2-DE analysis and LC-MS/MS identified CAPG protein as differentially expressed protein in tumor and non-tumor tissues of bladder cancer compared with normal tissues. Western blot analysis showed the CAPG overexpression in tumor tissues compared with normal tissues in a stage-dependent manner. Correspondingly, Real- time PCR showed a higher mRNA expression in tumoral bladder tissues than normal ones. CAPG mRNA overexpression had significantly a positive relation with tumor size (P = 0.019), the TNM staging (P = 0.001), and tumor differentiation (grade) (P = 0.006). Patients with lower levels of CAPG had higher recurrence-free survival in comparison with patients with higher levels (P = .027). Conclusion: CAPG overexpression was correlated with size, stage, grade, and shorter time to recurrence of bladder cancer. Therefore, CAPG overexpression could be related to poor prognosis of bladder cancer. These results suggest that CAPG may be considered as a prognostic factor and also for targeted therapy in bladder cancer. Moreover, it could be concluded that cancerous and noncancerous tissues of MIBC have the same protein expression because 2-DE results showed the CAPG expression in cancer and adjacent cancer tissues of bladder while CAPG was not detectable in normal tissues of bladder.